Delta expression in post-mitotic neurons identifies distinct subsets of adult-specific lineages in Drosophila. - Cornbrooks, C.; Bland, C.; Williams, D.W.; Truman, J.W.; Rand, M.D. (Developmental Neurobiology, 2007)
The Drosophila ventral nerve cord is comprised of numerous neuronal lineages, each derived from a stereotypically positioned neuroblast (NB). At the embryonic stage the unique identities of each NB, and several of their neuronal progeny, are well characterized by spatial and temporal expression patterns of molecular markers. These patterns of expression are not preserved at the larval stage and thus the identity of adult-specific lineages remains obscure. Recent clonal analysis using MARCM has identified 24 adult-specific lineages arising from thoracic NBs at the larval stage. In this study, we have explored a role for the Delta protein in development of the post-embryonic Drosophila ventral nerve cord. We find that Delta expression identifies 7 of the 24 adult-specific lineages of the thoracic ganglia by being highly enriched in clusters of newly born post-mitotic neurons and their neurite bundles. The Delta lineages constitute the majority of bundles projecting to the ventral neuropil, consistent with a role in processing leg sensory information. Targeted knockdown of Delta in neurons using RNAi results in significantly decreased leg chemosensory response and a relatively unaffected leg mechanosensory response. Delta RNAi knockdown in Delta lineages also gives a more diffuse bundle terminal morphology while the overall path-finding of neurite bundles is unaffected. We also identify a male-specific Delta lineage in the terminal abdominal ganglia, implicating a role for Delta in development of sexually dimorphic neural networks. Examples of Delta-expressing neurites contacting Notch-expressing glia are also seen, but are not common to all Delta lineages. Altogether, these data reveal a fundamental pattern of Delta expression that is indicative of an underlying developmental program that confers identity to adult lineage neurons.